SINTESIS DAN UJI POROSITAS SCAFFOLD HIDROKSIAPATIT/ALGINAT - Lalita El Milla; Decky J. Indrani; Bambang Irawan (Faculty of Dentistry, Universitas Islam Sultan Agung, 2018)
Background: In bone tissue engineering, scaﬀold is required with a large porosity of 80-90%. The porosity of the hydroxyapatite/alginate scaﬀold can be aﬀected by the alginate concentration used. The objective of this study was to determine whether hydroxyapatite/alginate scaﬀolds with alginate concentration of 1% and 3% could be synthesized and to determine whether the use of low concentration alginates in hydroxyapatite/alginate scaﬀolds could increase thescaﬀold porosity.Methods: The method used in making scaﬀold was freeze drying method, while the method used to measure porosity was liquid displacement methodResult: In this study, it was found that hydroxyapatite/1% alginate scaﬀolds porosity had greater porosity compared with hydroxyapatite/3% alginate scaﬀolds with signifcant diﬀerence.Conclusion: So, it can be concluded that the use of lower alginate concentration can increase porosity in hydroxyapatite/alginate scaﬀolds.